Role of Alcohol Metabolism in Chronic Pancreatitis - Vonlaufen, Alain (National Institute on Alcohol Abuse and Alcoholism, 2007)
Alcohol abuse is the major cause of chronic inflammation of the pancreas (i.e., chronic pancreatitis). Although it has long been thought that alcoholic pancreatitis is a chronic disease from the outset, evidence is accumulating to indicate that chronic damage in the pancreas may result from repeated attacks of acute tissue inflammation and death (i.e., necroinflammation). Initially, research into the pathogenesis of alcoholic pancreatitis was related to ductular and sphincteric abnormalities. In recent years, the focus has shifted to the type of pancreas cell that produces digestive juices (i.e., acinar cell). Alcohol now is known to exert a number of toxic effects on acinar cells. Notably, acinar cells have been shown to metabolize alcohol (i.e., ethanol) via both oxidative (i.e., involving oxygen) and nonoxidative pathways. The isolation and study of pancreatic stellate cells (PSCs)—the key effectors in the development of connective tissue fibers (i.e., fibrogenesis) in the pancreas—has greatly enhanced our understanding of the pathogenesis of chronic pancreatitis. Pancreatic stellate cells become activated in response to ethanol and acetaldehyde, a toxic byproduct of alcohol metabolism. In addition, PSCs have the capacity to metabolize alcohol via alcohol dehydrogenase (the major oxidizing enzyme for ethanol). The fact that only a small percentage of heavy alcoholics develop chronic pancreatitis has led to the search for precipitating factors of the disease. Several studies have investigated whether variations in ethanol-metabolizing enzymes may be a trigger factor for chronic pancreatitis, but no definite relationship has been established so far.